PbFe1/2Nb1/2O3 ceramics as a base material for electromechanical transducers - Bochenek, D.; Wawrzała, P. (Archives of Acoustics, 2006)
PbFe1/2Nb1/2O3 (PFN) material of perovskite structure has been rising interest because it connects both ferroelectric and antiferromagnetic properties. The paper presents tests of PFN ceramics obtained as a result of sintering simple oxides. As comparison, the base composition of the ceramics and composition with lithium admixture was synthesized. Densification was carried out using two methods: conventional sintering and hot pressing. XRD patterns, SEM micrographs of fractures surfaces, dielectric and electromechanical properties were performed.Admixing of PFN ceramics with a little amount of lithium allowed obtaining ceramics with better set of parameters from the point of view of their practical usage. The method of densification by hot pressing additionally improves these properties.